2021
DOI: 10.9787/pbb.2021.9.4.331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bentazone Reaction by Growth Stage and Bentazone Dose Across Soybean Genotypes

Abstract: Germplasm screening is time-consuming, labor-intensive, and expensive. Therefore, it is important to develop the most effective selection method for plant breeding and genetic studies. Herein, experiments were conducted to determine the optimal growth stage and application dose of bentazone based on the response of soybeans. The influence of soybean accessions, application doses (0X, 1X and 2X), and growth stages (VC, V1, V2) on plant injury and growth performance was examined. Leaf injury and growth performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Therefore, the age of the plant at which herbicides are applied determines the magnitude of the effect of the herbicides on the plant's growth parameters. Ali et al (2021) agreed with this when they reported the effect of bentazone application at different developmental stages on the growth parameters of soybean cultivars.…”
Section: Effect Of Nicosulfuron and Bentazone On The Growth Parameter...supporting
confidence: 71%
See 1 more Smart Citation
“…Therefore, the age of the plant at which herbicides are applied determines the magnitude of the effect of the herbicides on the plant's growth parameters. Ali et al (2021) agreed with this when they reported the effect of bentazone application at different developmental stages on the growth parameters of soybean cultivars.…”
Section: Effect Of Nicosulfuron and Bentazone On The Growth Parameter...supporting
confidence: 71%
“…Using herbicides significantly increases maize plants' yield due to effective weed control (Sharara et al 2005) and wheat (El-Rokiek et al 2022). Although bentazone herbicides are selective for maize, rice, cowpea, sorghum, soybeans, and peanut, however, its application at the different developmental stages of soybeans resulted in some visual injuries that impacted negatively on the growth of the plant (Ali et al 2021). The application of herbicides in crop fields, however, must be done at the appropriate time and dosage, as wrong timing for the application of postemergence herbicides, even at the recommended doses, could inflict some injuries on plants that might affect the grain size and yield or even kill the desirable plants (Legleiter and Johnson 2012;Varshney et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported that bentazone symptoms of Williams 82 were recovered after bentazone treatment [7,16]. Ali et al [58] mentioned that Williams 82 is a moderate-bentazone cultivar. In this study, moderate bentazone-tolerant cultivars were predominant in Korean soybeans, with a visual score ranging from 2.0-2.9 (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Injury was scored visually 5 days after treatment (DAT) when there were maximum injury symptoms on the leaves of the reference sensitive genotypes (Suwon 98 and PI 97150) [10]. The visual scoring scale is based on the area of leaf burn in our previous study [58]. A phenotypic scoring scale (1-5) was used to evaluate cultivar tolerance.…”
Section: Visual Determination Of Injurymentioning
confidence: 99%
See 1 more Smart Citation